Teachers’ Acceptability and Use of Accommodations for Students with Special Needs In The General Education Classrooms - Acdal, Mc Kerwin Niño (JPAIR Multidisciplinary Research, 2019)
Education for all and other related inclusive education memoranda and policies paved the way of teaching students with special needs in general education classrooms. In this context, one of the biggest tasks of general education teachers is to provide relevant and appropriate accommodations to students with special needs in their classes. Hence, accommodation is an indicator of successful execution of inclusion in several schools. This study aimed to examine the significant degree of relationship between the teachers’ acceptance and the use of accommodations for students with special needs in general education classrooms. Also, it employed a quantitative approach to research specifically the descriptive-correlational research design and adopted the Teacher Acceptability and Use Scale instrument Boulton, 2003. The data were obtained from the 70 teachers of Preschool to Grade 6 in Corpus Christi School- an institution that implemented a school-based policy on inclusive education. The results indicated assenting acceptance and use of accommodations in the general education classrooms. Also, it revealed a significant, strong, positive correlation between teachers’ acceptability and the use of accommodations. Lastly, while the teachers’ demographic profile is statistically controlled, it showed a significantly higher association between teachers’ acceptability and the use of accommodations.